Physiotherapists' use of suprascapular nerve blocks: an online survey. Issue 4 (December 2019) - Salt, Emma; Van Der Windt, Danielle; Chesterton, Linda; McRobert, Cliona; Foster, Nadine
Abstract: Background: There is some evidence to support the use of suprascapular nerve blocks (SSNBs) to manage shoulder pain. Although many patients with shoulder pain are referred to physiotherapy, there are no data describing whether physiotherapists currently use SSNBs for these patients. Objective: To explore if physiotherapists who manage musculoskeletal shoulder pain are using SSNBs and identify, of those who responded to an online questionnaire, how commonplace this practice is in the United Kingdom (UK) Design: An online, cross-sectional, questionnaire survey was developed for physiotherapists involved in the management of patients with shoulder pain. Methods: A snowball sampling method was used to invite physiotherapists to complete the online survey, using email, research advertisements in a professional magazine and via social media. The questionnaire captured respondents' demographic and professional practice characteristics, their knowledge and use of SSNBs and their views and experiences regarding SSNBs as a treatment for shoulder pain. Results: In total, there were 529 responders to the survey. Of these, 492 were eligible and formed the sample for analyses. The majority of responders (290/474; 61%) were from the UK. Of these, the majority (259/282; 92%) were familiar with SSNBs as a method of treatment for shoulder pain, although few (9/149; 6%) reported regularly using SSNBs in their clinical practice. Only 8 of 287 responders from the UK (3%) reported delivering SSNBs to patients. Conclusions: This survey provides preliminary evidence that the use and delivery of SSNBs by UK physiotherapists is uncommon. Future research is required to investigate the potential value of physiotherapists using this treatment option for their patients with shoulder pain.